2019
DOI: 10.1016/j.nicl.2019.101877
|View full text |Cite
|
Sign up to set email alerts
|

Frontopolar cortex activation associated with pessimistic future-thinking in adults with major depressive disorder

Abstract: Background Pessimistic thinking about the future is one of the cardinal symptoms of major depressive disorder (MDD) and is an important domain of cognitive functioning associated with hopelessness. Neuroimaging studies have shown that the frontopolar cortex (Brodmann area [BA] 10) is involved in thinking about the future and demonstrated that patients with MDD have dysfunctions in BA10. However, the relationship between pessimistic thinking about the future and brain activity is unclear. Hence, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…It has been proposed that BA10 serves as an integrative centre for higher order emotional, cognitive and social processes 23 24. In our previous study, we found that patients with MDD were associated with a greater propensity to engage in negative thinking about the distant future and exhibited increased activation in BA10 relative to healthy individuals when imagining the distant future 25. These obervations suggest that patients with MDD engage in pessimistic future thinking and experience difficulty in imagining their distant future, which is associated with abnormal patterns of frontal pole activity.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been proposed that BA10 serves as an integrative centre for higher order emotional, cognitive and social processes 23 24. In our previous study, we found that patients with MDD were associated with a greater propensity to engage in negative thinking about the distant future and exhibited increased activation in BA10 relative to healthy individuals when imagining the distant future 25. These obervations suggest that patients with MDD engage in pessimistic future thinking and experience difficulty in imagining their distant future, which is associated with abnormal patterns of frontal pole activity.…”
Section: Introductionmentioning
confidence: 71%
“…Based on the Future Thinking Implicit Relations Assessment Procedure developed by Kosnes and colleagues,43 we will use a modified version of the future-thinking task contextualised and adapted to Japanese culture 25. The future-thinking task uses an event design composed of four temporal conditions (distant future, near future, distant past and near past).…”
Section: Methodsmentioning
confidence: 99%
“…Immune activation does not seem be altered significantly by rTMS, rather stimulation of certain brain areas (increased functional connectivity of mFPC-BA10) and altered neurotransmitter production there might be affected. Further studies investigating biochemical pathways and specific brain areas in more detail might provide interesting new data (Riedel et al 2019 ; Katayama et al 2019 ; Rolls et al 2020 ). However, the so far already existing information on rTMS in patients with depression might offer a potential new treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…The medial frontopolar cortex [mFPC, Brodmann area 10 (BA 10)] and the amygdala play a major role in emotion and in mental disorders, probably relevant for novel treatment approaches in psychiatry (Riedel et al 2019 ). Neuroimaging studies have shown that patients with major depressive disorder have dysfunctions in BA 10 (Katayama et al 2019 ). New treatments increasing the activity and functional connectivity of the medial orbitofrontal cortex may be useful for treatment of depression (Rolls et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tonelli et al [32] reported that female suicide victims had increased levels of IL-4 and male suicide victims showed elevated levels of IL-13 compared to controls. Moreover, 24 teenager suicide victims had higher TNF-α, IL-1β, and IL-6 than normal control subjects in Brodmann area 10 [33], a brain region previously associated with suicidal ideation [34].…”
Section: Introductionmentioning
confidence: 99%